Employee engagement: A study of survivors in Indian IT/ITES sector - Binita Tiwari; Usha Lenka (IIMB Management Review, 2020)
This study aims to develop a conceptual framework of employee engagement in downsized organisations and further investigate its association with employer branding. A sample of 220 middle managers of Indian IT/ITES companies was selected. Structural equation modelling was used to evaluate the hypothesised model. Results indicate that internal corporate communication, knowledge sharing, continuous learning, intrapreneurship, and perceived communication satisfaction are positively associated with employee engagement. Employee engagement is also positively associated with employer branding. However, resonant leadership is negatively associated with employee engagement. The current study will help practitioners redesign their employee engagement practices to build a strong employer brand.